Economics and value based pricing - Williams, Iestyn (Henry Stewart Talks, 2010)
Pricing economics, Influence of demand characteristics, Elasticity, Relevance of cost attributes, Spillovers, Competitive effects, Differentiation strategies, Differential pricing and market segmentation, Bundling, Profit and welfare effects, Efficiency and distributional impact